2011
DOI: 10.1002/gps.2709
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological screening performance and the association with activities of daily living and instrumental activities of daily living in dementia: baseline and 18‐ to 24‐month follow‐up

Abstract: Objective: The use of neuropsychological assessment beyond diagnosis is related partly to the extent to which it can indicate everyday function. This study investigates whether the associations between neuropsychological functioning, activities of daily living (ADL) and instrumental activities of daily living (IADL) change over an 18-to 24-month follow-up, exploring whether these change with dementia progression.Method: Thirty-four patients with probable Alzheimer's disease were assessed at baseline and again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 41 publications
3
34
0
6
Order By: Relevance
“…Another study with a sample of 34 AD patients who were evaluated at baseline, 18 months, and 24 months later has found a strong relationship between cognition and IADL in the initial stages of AD. Such association becomes weaker as the disease progresses, increasing the association with psychiatric symptoms 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study with a sample of 34 AD patients who were evaluated at baseline, 18 months, and 24 months later has found a strong relationship between cognition and IADL in the initial stages of AD. Such association becomes weaker as the disease progresses, increasing the association with psychiatric symptoms 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study, using a refined and elegant prospective design, compared cognitive, behavioral and functional findings in the initial evaluation and after 24 months 20 . In this case, after compared correlations and linear regressions, authors concluded that during follow-up a positive association between cognitive abilities and instrumental activities tended to decrease, while direct relationship between instrumental impact and neuropsychiatric disorders increases.…”
Section: Discussionmentioning
confidence: 99%
“…IADLs are preferred to ADLs, as IADLs have been recently addressed as better indicators of emerging neuropsychiatric symptoms 5 . ADLs generally refer to basic activities of personal self-care (e.g., eating, dressing, washing), while IADLs are associated with more complex tasks, e.g., using the telephone, shopping groceries, organizing medications, and managing personal finances.…”
Section: Introductionmentioning
confidence: 99%
“…IADLs seem to be affected earlier than ADLs for early stage Alzheimer patients. We postulate that comparing data from several sensors could provide new (or at least complementary) quantitative evidence about changes in a patient's activities profile 5 . The clinical protocol' activities were specifically chosen according to their possibility of being realistically achieved into the observation room of the hospital and at the same time provide objective information about dementia symptoms.…”
Section: Introductionmentioning
confidence: 99%